Here's to us - Hilderbrand, Elin (New York : Little, Brown and Company, 2016)
Gathering at a ramshackle Nantucket cottage, a late celebrity chef's former wives and children confront the sources of their bitter rivalries and slowly let go of resentments as they remember positive times and share long-held secrets.
Keywords: Wives -- Fiction; Women -- Fiction; Loss (Psychology) -- Fiction; Wives -- Fiction; Women -- Fiction; Loss (Psychology) -- Fiction; Family -- Fiction; Nantucket Island (Mass.) -- Fiction; Nantucket Island (Mass.) -- Fiction; Domestic fiction